Superfícies isoperimétricas e a conjectura de Willmore no 3-espaço projetivo real - Yuri Juan Balcona Mamani (2015)
In this paper, we study the proof of the Willmore conjecture in the real projective space (...), made by A. Ross [24], which tells us for any torus immersed in the real projective space (...) with mean curvature H we have that (...) and that the equality is true if and only if is the minimal Clifford torus. In terms of immersed surfaces in (...), this result says that the Willmore conjecture is true for immersed tori in (...) invariant under the antipodal map.